LEGALITAS JUAL BELI PAKAIAN BEKAS IMPOR DI BANDA ACEH : Kajian Terhadap Fatwa DSN MUI No:110/DSN-MUI/IX/2017 Tentang Akad Jual Beli - Khalid Akbar; Safira Mustaqilla; Azka Amalia Jihad (Centre for Adat and Legal Studies of Aceh Province (CeFALSAP), 2025)
This study aims to determine how the system of buying and selling imported used clothing in Banda Aceh is viewed from the perspective of fiqh muamalah and to examine it in terms of the elements of gharar and the fatwa of DSN-MUI No: 110/DSN-MUI/IX/2017 concerning the contract of sale. This study employs a qualitative method using a legal-empirical approach. The findings reveal that the system of buying and selling imported used clothing in Banda Aceh involves three parties in the transaction: the seller, the buyer, and the distributor. The seller orders and purchases clothing from the distributor in the form of bags without being allowed to inspect the contents. Upon arrival, the clothing is sorted according to quality, washed thoroughly, and then sold to the buyer. In general, the practice of buying and selling imported used clothing in Banda Aceh aligns with the principles and conditions of Islamic sales transactions. However, when examining the transactions between sellers and distributors of imported used clothing, there is an element of gharar, which involves uncertainty about the goods being purchased, as sellers are not permitted to inspect the goods in the bags before they are shipped. This falls under the category of gharar, which is not permitted in Islam.